2023
DOI: 10.1101/2023.07.18.549479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drosophilaaxis extension is robust to an orthogonal pull by invaginating mesoderm

Abstract: As tissues grow and change shape during animal development, they physically pull and push on each other and these mechanical interactions can be important for morphogenesis. During Drosophila gastrulation, mesoderm invagination temporally overlaps with the extension of the ectodermal germband; the latter is caused primarily by Myosin II-driven polarised cell intercalation. Here we investigate the impact of mesoderm invagination on ectoderm extension, examining possible mechanical and mechanotransductive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It has recently been proposed that the stretch from ventral furrow invagination recruits myosin to cell junctions in the germband in a planar polarized fashion via mechanical feedback mechanisms, which then promote tissue flow [18]. However, other studies have shown that myosin planar polarity acts downstream of AP patterning systems [6,7,21] and have shown that the germband displays cell rearrangements and tissue elongation even when the ventral furrow is disrupted [10,13,44,45]. Here, we find delays in disorder, cell rearrangement, and tissue elongation in sna twi mutant embryos, suggesting that the ventral furrow facilitates but is not required for tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been proposed that the stretch from ventral furrow invagination recruits myosin to cell junctions in the germband in a planar polarized fashion via mechanical feedback mechanisms, which then promote tissue flow [18]. However, other studies have shown that myosin planar polarity acts downstream of AP patterning systems [6,7,21] and have shown that the germband displays cell rearrangements and tissue elongation even when the ventral furrow is disrupted [10,13,44,45]. Here, we find delays in disorder, cell rearrangement, and tissue elongation in sna twi mutant embryos, suggesting that the ventral furrow facilitates but is not required for tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%